Erratum. (June 2018) - Unknown
The below articles were initially published using different digital object identifier (DOI) numbers. The original DOIs included the number 23115024. The number 23115024 in each DOI has been updated to 23315024 to reflect the journal's current ISSN. The specific changes are as follows: The DOI10.1177/2311502418767088 has been corrected to10.1177/2331502418767088 The DOI10.1177/2311502418765404 has been corrected to10.1177/2331502418765404 The DOI10.1177/2311502418765414 has been corrected to10.1177/2331502418765414 The DOI10.1177/2311502418771915 has been corrected to10.1177/2331502418771915 The complete references for the impacted articles are as follows: Albahari, Maurizio. 2018. "From Right to Permission: Asylum, Mediterranean Migrations, and Europe's War on Smuggling." Journal on Migration and Human Security 6(2):121–30.https://doi.org/10.1177/2331502418767088 . Flores-Yeffal, Nadia Y., and Karen A. Pren. 2018. "Predicting Unauthorized Salvadoran Migrants' First Migration to the United States between 1965 and 2007." Journal on Migration and Human Security 6(2):131–44.https://doi.org/10.1177/2331502418765404 . Gilman, Denise, and Luis A. Romero. 2018. "Immigration Detention, Inc." Journal on Migration and Human Security 6(2):145–60.https://doi.org/10.1177/2331502418765414 . Atkinson, Jeanne M., and Tom K. Wong. 2018. "The Case for a National Legalization Program without Legislation or Executive Action: Results from Screening for Immigration Legal Options." Journal on Migration and Human Security 6(2):161–166.https://doi.org/10.1177/2331502418771915 .